2018 21st International Conference of Computer and Information Technology (ICCIT) 2018
DOI: 10.1109/iccitechn.2018.8631925
|View full text |Cite
|
Sign up to set email alerts
|

Total Recall: Understanding Traffic Signs Using Deep Convolutional Neural Network

Abstract: Recognizing Traffic Signs using intelligent systems can drastically reduce the number of accidents happening worldwide. With the arrival of Self-driving cars it has become a staple challenge to solve the automatic recognition of Traffic and Hand-held signs in the major streets. Various machine learning techniques like Random Forest, SVM as well as deep learning models has been proposed for classifying traffic signs. Though they reach state-of-the-art performance on a particular dataset, but fall short of tackl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Traditional object detection algorithms are still widely used for fast calculation speed and low memory footprint [10][11][12][13] . For example, Anant Ram Dubey [14] et al used HOG-SVM method to detect road objects, and Takaki Masanari [15] used SIFT [6] method to detect traffic signs.…”
Section: Related Workmentioning
confidence: 99%
“…Traditional object detection algorithms are still widely used for fast calculation speed and low memory footprint [10][11][12][13] . For example, Anant Ram Dubey [14] et al used HOG-SVM method to detect road objects, and Takaki Masanari [15] used SIFT [6] method to detect traffic signs.…”
Section: Related Workmentioning
confidence: 99%
“…The result in Table 3 provides a comparison of the classification accuracy between ROSST, the proposed method, and some state-of-the-art supervised learning algorithms, which include single CNN with three STNs [29], DCGAN-PILAE [30], traffic sign classification based on pLSA [16], multiscale CNNs [31], BAGAN [32], traffic sign recognition with hinge loss CNNs (HLSGD) [49], and residual blocks CNN [50]. All these state-of-the-art methods were evaluated on the GTSRB dataset, making it fair to compare the proposed method ROSST with them.…”
Section: Attention Cropping K C Self-training Acc (%) F1 (%) Precisiomentioning
confidence: 99%
“…This occurred because those frameworks had accuracy rates that were higher than the proposed method. The state-of-the-art models [29,30,49,50] used all of the training set to train the model and then were tested on the test set, but the proposed method used 60% of the training data to train and validate the model during the supervised training stage and later ran on the unlabeled set(the remainder of training plus the test sets) for the self-paced learning phase. This showed that the model could perform well and achieve a higher recognition rate on a small set of data and train a good model just as the state-of-the-art models.…”
Section: Attention Cropping K C Self-training Acc (%) F1 (%) Precisiomentioning
confidence: 99%
See 2 more Smart Citations